Pengaruh Pemberian Ekstrak Daun Pule (Alstonia scholaris) Yang Dienkapsulasi Terhadap Berat Non Karkas Ayam Broiler Yang Dipelihara Pada Kepadatan Tinggi - Fadli Fadli; Yusnaini Yusnaini; Eny Endrawati; Nur Sjafani; MA Salim; Yusri Sapsuha (Jurnal Pertanian Khairun, 2026)
This study aims to determine the effect of encapsulated pule leaf extract (Alstonia scholaris) on the percentage of non-carcass in broiler chickens raised at high density. The in vivo experiment used 189 broiler chicks divided into five treatments and each treatment was repeated five times, namely T0 (negative control with a normal density of 7 chicks/m2), T1 (positive control with a high density of 14 chicks/m2), T2, T3, and T4 with a high density of 14 chicks/m2. Encapsulated pule leaf extract was added to the feed from the 8th day at 0.5, 1.0, and 1.5 g/kg feed for T2, T3 and T4, respectively. On the 28th day, non-carcass organs were measured. There was no difference (p>0.05) in the weight and percentage of non-carcass in broiler chickens. It can be concluded that encapsulated pule leaf extract can be used as a feed additive in broiler chickens because it can increase slaughter weight and does not have a detrimental effect on broiler chickens.